HUBUNGAN PENGETAHUAN, SIKAP DAN PERILAKU IBU TENTANG PERSONAL HYGIENE DENGAN KEJADIAN DIARE PADA ANAK DI RUMAH SAKIT X - Melly Putri; Nopi Nur Khasanah; Indra Tri Astuti (Journal Healthcare Education, 2026)
One of the factors that plays an important role in preventing diarrhea is the implementation of personal hygiene, especially by mothers as the primary caregivers of children. The role of mothers in implementing personal hygiene through appropriate knowledge, attitudes, and behavior is important to prevent diarrhea, so it is necessary to study its relationship with the incidence of diarrhea in children. Objective: This study aims to determine the relationship between knowledge, attitudes, and behavior of mothers about personal hygiene with the incidence of diarrhea in children in the Pediatric Ward of Sari Asih Hospital, Serang. Method: Quantitative research with a cross-sectional design involving 73 pediatric patients taken using a purposive sampling technique. The research instrument used a questionnaire. Data analysis with the Spearman rank test. Results: The results of univariate analysis showed that the majority of mothers in the Pediatric Ward of Sari Asih Hospital, Serang were aged 20-30 years (57.5%), high school (43.8%), housewives (61.6%). Knowledge was quite good (43.8%). Positive attitude (53.4%). Personal hygiene behavior was good (63%), and the majority of children experienced diarrhea (53.4%). The results of the bivariate analysis showed that maternal knowledge (p-value: 0.000), maternal attitudes (p-value: 0.001), and maternal personal hygiene behavior were associated with the incidence of diarrhea in the Pediatric Ward of Sari Asih Hospital, Serang. Conclusion: There is a relationship between maternal knowledge, maternal attitudes, and maternal personal hygiene behavior with the incidence of diarrhea in the Pediatric Ward of Sari Asih Hospital, Serang.